Reading comprehension strategies for the Filipino second language reader in a bilingual context - Otero, Marietta Reyes (2004)
This paper presents the theoretical and practical applications of the social-constructivist viewpoint and the cognitive academic language proficiency perspective in the development of reading comprehension among second language readers in the Philippines. Varied and numerous strategies for developing comprehension are included in this paper that teachers can adapt during teaching.
Keywords: Reading comprehension -- Research; Reading strategies; Second language acquisition